Strategi Pengembangan Ekosistem Keuangan (Close Payment) Cluster Bisnis Pertanian Jagung pada BRI KCP Tiga Binanga - Joeanda, Joeanda; Sembiring, Meilita Tryana; Pujangkoro, Sugiharto (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to identify internal and external factors that become obstacles in the development of the financial ecosystem (close payment) of the agricultural business cluster at BRI KCP Tiga Binanga and to develop appropriate strategies using the SWOT analysis method (strengths, weaknesses, opportunities and threats) and QSPM (quantitative strategic planning matrix). The results of the QSPM analysis (quantitative strategic planning matrix) of priority strategies in the development of the financial ecosystem (Close Payment) in the Corn Agricultural Business Cluster are that employees provide socialization about the use of mobile banking at BRI KCP Tiga Binanga.